Perspektif Islam Membangun Kepemimpinan Perempuan dalam Pendidikan Inklusif - Zussiana Elly Triantini (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: As universal system of values, Istam does not tend to support any descrimination based sn any kinds of social differences, i.e. cultrure, religion, and gender. Islm actually acknowledges human differences. However, they are not seen as social basis for descrimination but as a way to construct just culture and structure within pluralistic people so all people live together harmoniously. In the case of gender equity in ruting education, female has opportunity and great potens to success in ruting education since the education buitt within inclusive gender paradigma. This paper tries to promote alternative way in understand texts within sociohistorical contexts concerning the female chance to be principle for education. As welt, it also promote alternative way in stucturing theory of inclusive education within femate leadership. Keywords: Islam, Gender Equity, Inclusive, Education, and Female leadership